Presentation is loading. Please wait.

Presentation is loading. Please wait.

CuS+HNO 3 →Cu(NO 3 ) 2 + S + NO+H 2 O. CuS -2 +HN +5 O 3 →Cu(NO 3 ) 2 + S 0 + N +2 O+H 2 O.

Similar presentations


Presentation on theme: "CuS+HNO 3 →Cu(NO 3 ) 2 + S + NO+H 2 O. CuS -2 +HN +5 O 3 →Cu(NO 3 ) 2 + S 0 + N +2 O+H 2 O."— Presentation transcript:

1 CuS+HNO 3 →Cu(NO 3 ) 2 + S + NO+H 2 O

2 CuS -2 +HN +5 O 3 →Cu(NO 3 ) 2 + S 0 + N +2 O+H 2 O

3 CuS+HNO 3 →Cu(NO 3 ) 2 + S + NO+H 2 O CuS -2 +HN +5 O 3 →Cu(NO 3 ) 2 + S 0 + N +2 O+H 2 O N +5 + 3e → N +2

4 CuS+HNO 3 →Cu(NO 3 ) 2 + S + NO+H 2 O CuS -2 +HN +5 O 3 →Cu(NO 3 ) 2 + S 0 + N +2 O+H 2 O N +5 + 3e → N +2 S -2 – 2e → S 0

5 CuS+HNO 3 →Cu(NO 3 ) 2 + S + NO+H 2 O CuS -2 +HN +5 O 3 →Cu(NO 3 ) 2 + S 0 + N +2 O+H 2 O N +5 + 3e → N +2 S -2 – 2e → S 0 6 2 3

6 CuS+HNO 3 →Cu(NO 3 ) 2 + S + NO+H 2 O CuS -2 +HN +5 O 3 →Cu(NO 3 ) 2 + S 0 + N +2 O+H 2 O N +5 + 3e → N +2 S -2 – 2e → S 0 6 2 3

7 CuS+HNO 3 →Cu(NO 3 ) 2 + S + NO+H 2 O CuS -2 +HN +5 O 3 →Cu(NO 3 ) 2 +3S 0 +2N +2 O+H 2 O N +5 + 3e → N +2 S -2 – 1e → S 0 3 1 3

8 CuS + HNO 3 →Cu(NO 3 ) 2 + 3S +2NO + H 2 O 3CuS + HNO 3 → Cu(NO 3 ) 2 + 3S+ NO + H 2 O 3CuS + HNO 3 → 3Cu(NO 3 ) 2 + 3S + 2NO + H 2 O

9 3CuS +8HNO 3 → 3Cu(NO 3 ) 2 +3S +2N O+H 2 O 3CuS + 8HNO 3 → 3Cu(NO 3 ) 2 + 3S + 2NO + 4H 2 O

10 184 2 24 24


Download ppt "CuS+HNO 3 →Cu(NO 3 ) 2 + S + NO+H 2 O. CuS -2 +HN +5 O 3 →Cu(NO 3 ) 2 + S 0 + N +2 O+H 2 O."

Similar presentations


Ads by Google